Composition and metabolizable energy of feed used by fallow deer (Dama dama) in a coastal Mediterranean ecosystem - Poli, B M; Focardi, S; Tinelli, A (Small Ruminant Research, 1996)
Data on the impact of a population of about 1000 (spring estimate) fallow deer (Dama &ma) on eight shrubs and mono- and dicotyledonous plants were collecred in a coastal Mediterranean environment from December 1990 to March 1992. Four species of shrubs (Cistus salvifoiius, Phillyrea larifolia, Rubus ulmifolius. Quercus ibex) and mixed graminoids were preferentially consumed. In autumn-winter the acorns of several species, Q. cerris and Q. ilex in particular, were also consumed. We determined the chemical composition, in vivo digestibility coefficients and metabolizable energy content of the feed. On average, R. ulmifolius had the lowest fibre content (18% DM) and the highest protein content (12% DM), organic matter digestibility (59%) and metabolizable energy value (2083 kcal ME kg- ’ DM). C. saluifolius, P. fafifolia and mixed graminoids did not differ significantly in organic matter digestibility (OMD) and nutritive value (I 801, 1765 and 1557 kcal ME kg-’ DM, respectively), while Q. ilex had the lowest nutrient estimates with 32% OMD and 1362 kcal ME kg-’ DM. Forage quality traits usually peaked in spring and autumn. Metabolizable energy was positively correlated with protein, neutral detergent fibre and N-free extractives contents, and negatively correlated with the acid detergent fibre content. Acorns were generally highly digestible; in particular, the seed of Q. farniu and Q. ilex showed 80% and 83% OMD, respectively. In a Mediterranean environment the summer seems the most critical season for fallow deer. The results of this work are important for assessing the carrying capacity of wild Mediterranean ecosystems for fallow deer.
Keywords: digestibility; Fallow deer; Feed quality; in vitro; Mediterranean ecosystems